CLINICAL EVALUATION OF KARNAPOORANA IN SENSORINEURAL HEARING LOSS: AN AYURVEDIC PERSPECTIVE ON KARNABADHIRYA - Dr. Jayvant vasant Kharat; Dr. Manjiri Pritam Keskar (The Bioscan, 2025)
This study evaluated the therapeutic potential of Karnapoorana, an Ayurvedic intervention, in the management of sensorineural hearing loss (SNHL). A randomized controlled trial was carried out with 100 participants, equally divided into an experimental group (n = 50) and a control group (n = 50). The experimental group received daily Karnapoorana therapy for 30 days, while the control group was administered a placebo. Outcomes were assessed using Pure Tone Audiometry (PTA) and the Hearing Handicap Inventory for Adults (HHIA) at baseline (Day 0), end of treatment (Day 30), and follow-up (Day 60). The experimental group demonstrated a statistically significant improvement in hearing thresholds compared to the control group. At Day 30, the mean PTA improvement in the intervention group was 5 dB HL, whereas the control group showed a smaller gain of 3.1 dB HL. Furthermore, HHIA scores reflected greater psychosocial benefits among participants in the treatment arm, with a mean reduction of 15.3 points compared to 4.8 points in the control group.